Cloning & expression of glucose oxidase from Aspergillusniger - SUMAIYA SHAIKH; RATNA TRIVEDI (International Journal of Pharma and Bio Sciences, 2016)
Our aims is to clone the Glucose oxidase (GOx) gene which has been isolated from Aspergillus niger, in turn isolated from the fertile garden soil. Detection of the expression of gox gene in prokaryotic host. Aspergillus niger has been isolated from soil samples taken from Navsari region. Enzyme assay has been done to check enzyme. DNA extraction & PCR amplification was done using Banglore GeNeiTM kits. 90% success has been achieved by obtaining the GOx protein from Escherichia coli BL21 in inclusion bodies. The protein has been purified onto Ni-NTA column. gox gene was successfully isolated and expressed in prokaryotic host, which would be purified by simple procedure. –We conclude that the by-product of gluconic acid fermentation has a great industrial importance. So, for greater production of GOx, the gene can be transferred from donor to the recipient. The gox gene of Aspergillus niger has been isolated and studied for the identification & its expression for improvement of enzyme production by establishing a process based on heterologous expression.